2014
DOI: 10.4155/tde.14.31
|View full text |Cite
|
Sign up to set email alerts
|

Skin Delivery Aspects of Benzoyl Peroxide-Loaded Solid Lipid Nanoparticles for Acne Treatment

Abstract: Desired goals were achieved by factorial design approach in shortest possible time with minimum number of experiments. The developed BPO-SLN system provided controlled drug release, thereby reducing the well-known side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…21 Benzoyl peroxide-loaded SLN showed a higher drug deposition in skin organelles, lower skin irritation, sustained drug release, lower drug absorption to the systemic circulation, and reduced adverse effects in comparison with available marketed formulations. 23 Lipid nanoparticles are promising carriers for the topical delivery of lipophilic drugs with high log P values (log P>3) and large molecular weights. Because of their lipidic nature, SLNs have higher entrapment efficiency and penetrate deeply through skin layers.…”
Section: Solid Lipid Nanoparticles (Slns)mentioning
confidence: 99%
“…21 Benzoyl peroxide-loaded SLN showed a higher drug deposition in skin organelles, lower skin irritation, sustained drug release, lower drug absorption to the systemic circulation, and reduced adverse effects in comparison with available marketed formulations. 23 Lipid nanoparticles are promising carriers for the topical delivery of lipophilic drugs with high log P values (log P>3) and large molecular weights. Because of their lipidic nature, SLNs have higher entrapment efficiency and penetrate deeply through skin layers.…”
Section: Solid Lipid Nanoparticles (Slns)mentioning
confidence: 99%
“…The optimized SLN (F4) was successfully incorporated into the carbopol-based hydrogel. The comparison in vitro release of ERY from the SLN gel showed 90.94% and plain gel showed 87.94% .Therefore concluding that In vitro study of ERY-loaded SLN gel showed sustained delivery of drug from formulation thus enhancing the antimicrobial activity after 30 hours when compared to ERY plain gel (20).…”
Section: Solid Lipid Nanoparticles Slnmentioning
confidence: 77%
“…It has been demonstrated that reducing the drug particle size to the nanometer range in diameter using SLNs provides effective ocular tissue penetration and resolution of pain and inflammation despite a reduced drug concentration (0.38%) and dosing frequency (Salinger et al, 2019). Benzoyl peroxide SLN has demonstrated higher drug accumulation in lower skin inflammation, skin organelles, continuous release of drugs, lower systemic absorption of drugs, and decreased adverse effects relative to the current marketing formulations (Pokharkar et al, 2014). Lipid NPs are significant carriers for lipophilic drugs for topical delivery having high log P-values (logP > 3) and maximum molecular weight (≤500).…”
Section: Solid Lipid Nanoparticles (Slns)mentioning
confidence: 99%